COMPARING ORAL PARACETAMOL DOSES IN PAEDIATRICS WITH THE NEW BNF-C DOSING. Issue 9 (17th August 2016) - Ajjan, Nour; Shenton, Sian
Abstract : The BNF-C 2014–20151 highlighted some key changes to the dosing of paracetamol in paediatrics, including a change in maximum daily dosage of oral paracetamol from 90 mg/kg/day to 75 mg/kg/day for post-operative pain, and inclusion of age-banded dosing for pain and pyrexia. The local Trust Paediatric Acute Pain Management Manual2 has acknowledged this change, but advised a maximum daily dose of 80 mg/kg/day. This audit was undertaken to determine whether national proposed changes were implemented in practice, in comparison with local guidelines. Aims: The aims and objectives of the audit were to compare oral paracetamol dosing in both medical and surgical settings with the new BNF-C dosing. Method: Data were collected over a two week period in September 2014, from two medical and two surgical paediatric wards. The criteria for data collection included paediatric patients above the age of one month and up to 18 years, prescribed oral paracetamol for pain or pyrexia. The following data were collected: ▸ Initials of patients and age (for identification purposes and to prevent duplications) ▸ Weight (to assess appropriate and safe prescribing) ▸ Reason for admission (to distinguish between medical and surgical settings). Results: Data were collected from 24 medical and 48 surgical patients (age range 1 month–16 years). The key findings were: 19/24 medical patients were dosed according to the BNF-C age banded guidelines; 5/24 were dosed according to weight: 3 followed the Trust Manual; 1/24 followed the BNF-C, and 1 miscellaneous. No patients had a dose exceeding 80 mg/kg/day. 87% of surgical patients were dosed according to the weight based calculation, 69% of whom were within the maximum daily dose of 75 mg/kg. Of the 31% whose daily dose exceeded 75 mg/kg, all were less than 80 mg/kg/day. The Trust Pain Manual does not include the dose banding as per the BNF-C but recommends 20 mg/kg 6 hourly (max 80 mg/kg/day) for acute pain in this age group. Conclusion: Children on the medical wards were prescribed paracetamol following age banded dosing as per BNF-C, whereas surgical wards were more likely to dose by weight following the Trust Pain Manual. The Trust Pain Manual differs from the BNF-C and recommends a maximum daily dose of 80 mg/kg/day for acute severe pain, to ensure adequate pain control and minimise calculation errors. Despite the new guidance in the BNF-C, it was found that many patients were prescribed a maximal daily dose greater than 75 mg/kg/day; however no patient's daily dose exceeded 80 mg/kg/day as indicated in the Manual. The main finding from the audit was that prescribers were not aware of the change in maximal daily dose of oral paracetamol. To highlight this important point, a poster was designed and distributed amongst the medical and surgical staff on the wards, highlighting that the dose should not exceed 75 mg/kg in a 24 hour period.